2016
DOI: 10.1186/s41182-016-0024-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-trypanosome effects of nutritional supplements and vitamin D3: in vitro and in vivo efficacy against Trypanosoma brucei brucei

Abstract: BackgroundPrevious publications suggest that nutritional supplements have anti-trypanosome activity in vitro, although apparent efficacy was not noted in vivo. This study was conducted by experimentally infecting mice with Trypanosoma brucei brucei to assess the anti-trypanosome activity of various nutritional supplements with the hope of finding possible application in the treatment of African trypanosomiasis.MethodsActivities of nutritional supplements were screened in vitro against bloodstream forms of T. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…SalB is another compound present in oregano extracts at a high concentration. It is frequently found in potentially immunomodulatory substances that are active in vitro, however, its effects do not appear to be translatable to an in vivo system [17]. In the present research, the in vitro anti-inflammatory potential of SalB was mediated by a reduction of TNF from macrophages, which is in accordance with the study of Sun et al (2016), who also showed that SalB downregulated TNF secretion [18].…”
Section: Discussionsupporting
confidence: 90%
“…SalB is another compound present in oregano extracts at a high concentration. It is frequently found in potentially immunomodulatory substances that are active in vitro, however, its effects do not appear to be translatable to an in vivo system [17]. In the present research, the in vitro anti-inflammatory potential of SalB was mediated by a reduction of TNF from macrophages, which is in accordance with the study of Sun et al (2016), who also showed that SalB downregulated TNF secretion [18].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, vitamin C has been shown to potentiate the trypanocidal effects of diminazene aceturate in a co-administration trial ( Chekwube et al, 2014 ). More recently, vitamin D3 has shown some efficacy in protecting the host during T. brucei infection, however the mechanism of action is not yet known ( Jamal et al, 2016 ).…”
Section: Host-targeted Therapeutics and Approaches For Treatment Of Hmentioning
confidence: 99%
“…In addition, some studies have shown antitrypanosomal activity of vitamins and their antioxidant property may help ameliorate toxicity, which is a characteristic of many trypanocides. The antitrypanosomal activities of vitamin C, vitamin D3 and vitamin E been demonstrated in vitro with IC5O of 58.6 μM, 4.58 μM and 28.6 μM respectively in T. b. brucei (Jamal et al, 2016). Likewise, in mice infected with T. b. brucei, treatment with 250 and 500 ng/Kg vitamin D3 resulted in significant decrease in parasitaemia, significant suppression of splenomegaly and recovery from declined RBC compared with non-treated control mice, although there was no detectable difference in body weight (Jamal et al, 2016).…”
Section: Use Of Vitamins and Immune Modulatorsmentioning
confidence: 99%